2022
DOI: 10.1111/tpj.15739
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome‐level genome of Camellia lanceoleosa provides a valuable resource for understanding genome evolution and self‐incompatibility

Abstract: The section Oleifera (Theaceae) has attracted attention for the high levels of unsaturated fatty acids found in its seeds. Here, we report the chromosome-scale genome of the sect. Oleifera using diploid wild Camellia lanceoleosa with a final size of 3.00 Gb and an N50 scaffold size of 186.43 Mb. Repetitive sequences accounted for 80.63% and were distributed unevenly across the genome. Camellia lanceoleosa underwent a whole-genome duplication event approximately 65 million years ago (65 Mya), prior to the diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 72 publications
2
25
0
Order By: Relevance
“…Previous studies have confirmed that cultivated tea plants ( C. sinensis ), similar to many other flowering plants, have experienced a recent WGD event 30–40 MYA (Wang et al., 2021; Xia et al., 2017b); however, it is still unclear whether this WGD event occurred in other Camellia plants, as well as how it affects the diversification and quality traits of Camellia plants. Our results offered supplemental evidence demonstrating that the most recent common ancestor of Camellia plants such as cultivated tea plants, wild tea plants, and oil tea plants shared a recent WGD event with Ericales such as kiwifruit through genomic collinearity analysis (Gong et al., 2022; Xia et al., 2020b, Zhang et al., 2020b) (Figure S1d). Functional annotation of the WGD‐derived duplicated genes of three representative Camellia plants, including cultivated tea plant ( C. sinensis ), oil‐tea plant ( C. oleifera ), and common camellia ( C. reticulata ), revealed that some of these duplicated genes derived from WGD events were associated with UDP‐glycosyltransferase activity, lipid biosynthetic process, aromatic compound biosynthetic process, and pigment metabolic process.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies have confirmed that cultivated tea plants ( C. sinensis ), similar to many other flowering plants, have experienced a recent WGD event 30–40 MYA (Wang et al., 2021; Xia et al., 2017b); however, it is still unclear whether this WGD event occurred in other Camellia plants, as well as how it affects the diversification and quality traits of Camellia plants. Our results offered supplemental evidence demonstrating that the most recent common ancestor of Camellia plants such as cultivated tea plants, wild tea plants, and oil tea plants shared a recent WGD event with Ericales such as kiwifruit through genomic collinearity analysis (Gong et al., 2022; Xia et al., 2020b, Zhang et al., 2020b) (Figure S1d). Functional annotation of the WGD‐derived duplicated genes of three representative Camellia plants, including cultivated tea plant ( C. sinensis ), oil‐tea plant ( C. oleifera ), and common camellia ( C. reticulata ), revealed that some of these duplicated genes derived from WGD events were associated with UDP‐glycosyltransferase activity, lipid biosynthetic process, aromatic compound biosynthetic process, and pigment metabolic process.…”
Section: Discussionmentioning
confidence: 63%
“…The tea plant is one of the most significant and traditional economic crops grown in Asia, Africa, and Latin America, whose leaves are used to produce numerous kinds of tea [ 2 , 3 , 4 ]. Camellia oleifera is a woody oil plant, whose seed kernels produce abundant edible oils with high monounsaturated fatty acid content [ 5 , 6 , 7 ]. The planting area for C. oleifera was about 4.39 million hectares in China with a total output value of 116 billion RMB [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Camellia oleifera is a woody oil plant, whose seed kernels produce abundant edible oils with high monounsaturated fatty acid content [ 5 , 6 , 7 ]. The planting area for C. oleifera was about 4.39 million hectares in China with a total output value of 116 billion RMB [ 6 ]. It has been utilized extensively in France, Japan, and the USA, as a source of additive for cosmetics [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an abundance of genomic information has been generated for C. oleifera . The published genome of Camellia lanceoleosa provides an important reference for analyzing the formation and regulation of important traits such as self-incompatibility and lipid synthesis ( Gong et al, 2022 ). Construction of a high-quality reference genome at the chromosome level of C. oleifera has demonstrated that the alleles regulating the synthesis of C. oleifera have been under artificial selection, and this genome resource could provide new insights with implications for the genetic improvement of C. oleifera varieties ( Lin et al, 2022 ).…”
Section: Research On the Biology Of C Oleiferamentioning
confidence: 99%